2012
DOI: 10.1155/2012/519467
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Aldosterone Synthesis and Secretion by Channel Antagonists

Abstract: Aldosterone, a specific mineralocorticoid receptor (MR) agonist and a key player in the development of hypertension, is synthesized as a final product of renin-angiotensin-aldosterone system. Hypertension can be generally treated by negating the effects of angiotensin II through the use of angiotensin-converting enzyme inhibitors (ACE-Is) or angiotensin II type 1 receptor antagonists (ARBs). However, the efficacy of angiotensin II blockade by such drugs is sometimes diminished by the so-called “aldosterone bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
7
1
1
Order By: Relevance
“…This result may be because in our study, cases were young, healthy adults, while in other studies, cases were hypertensive individuals. This study differs from the study in Japan [11], which showed a significantly different in the level of plasma aldosterone in the hypertensive groups. Additionally, the highest level of aldosterone was found in individuals with the CC genotype, compared with those with the TC and TT genotypes, and individuals with the TC + CC genotype had higher aldosterone levels than those with the TT genotype.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result may be because in our study, cases were young, healthy adults, while in other studies, cases were hypertensive individuals. This study differs from the study in Japan [11], which showed a significantly different in the level of plasma aldosterone in the hypertensive groups. Additionally, the highest level of aldosterone was found in individuals with the CC genotype, compared with those with the TC and TT genotypes, and individuals with the TC + CC genotype had higher aldosterone levels than those with the TT genotype.…”
Section: Discussioncontrasting
confidence: 99%
“…The TC and CC genotypes were higher in cases than in the controls, and they were risk factors for hypertension. This result was consistent with studies carried out in Japanese [11] and Chinese populations [13]. The TC + CC genotypes were more common in hypertensive patients compared with normotensive patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several dihydropyrine calcium channel antagonists weakly antagonize the mineralocorticoid receptor or inhibit key enzymes of aldosterone biosynthesis (most notably CYP1B2). 73,74 Nifedipine, nitrendipine and felodipine are the available molecules with the greatest antialdosterone potency. Nifedipine has been tested as a monotherapy in 10 PA patients, and was shown to have a significant effect on BP, serum potassium and aldosterone concentrations at four weeks.…”
Section: Drug-based Treatment For Pamentioning
confidence: 99%
“…1 In past years, interactions between cations and secretagogeous, in the process of hormone release have been studied by examining the effects of various organic calcium antagonists upon isolated secretory tissues. 2 The effects of these agents are overcome by increased concentration of extracellular calcium. Because of high activity and apparent selection of these agents, their activity in other systems can be viewed as evidence that basically slow calcium channels are operative in variety of secretory processes.…”
Section: Introductionmentioning
confidence: 99%